Relógios de Sol nas aulas de Matemática: construção do conhecimento através da prototipagem - Lopes, Jorge Luis da Costa (2017)
The study focused on this dissertation was carried out at the Colégio Estadual Alaor Coutinho - CEAC, located in Praia do Forte, municipality of Mata de São João - Bahia, a college in which a large part of the students in the academic years of 2014 and 2015 reported, in the classroom, greater difficulties of understanding the subjects related to Trigonometry and Geometry. In an attempt to reverse this situation and facilitate the learning of existing subjects in Trigonometry and Geometry, basic astronomical knowledge related to sundials, allied to concepts of Geography with respect to Geographic Coordinates and Earth Movements, were used. Activities were carried out with students from Elementary and Middle School, such as: workshops, classes and events related to the construction and positioning of Sun Clocks. As a final product, we made different Equatorial Type Sun Clocks, as well as a Didactic Sequence for teachers of education basic.